Assessment Of The Risk Of Plug Or Water Barrier Failure Due To Seismicity At South Deep Mine (The Southern African Institute of Mining and Metallurgy, 2006)
As part of a comprehensive risk analysis which was carried out into the effectiveness of the water barrier between South Deep and Randfontein Estate mines, the potential threat posed by large seismic events was assessed. The study covered several aspects. Firstly, an estimate of the maximum credible earthquake was obtained from a probabilistic analysis of the regional seismicity of the previous 25 years. Allowance was made for ?reservoir-induced? effects by increasing the estimate of the size of the maximum credible earthquake from ML= 5.1 to ML= 5.5. Based on available knowledge of the geological structure, the possibility of such an event occurring in the vicinity of the barrier pillar was estimated. The possibility of substantial damage to the barrier rock mass, resulting as a consequence of a large event, was assessed. The likely damage to the concrete control plugs installed in five tunnels that penetrated the barrier, which might result from a ?near-miss? by the largest possible seismic event or from a ?direct hit? by a smaller event, was also considered. It was concluded that there was a negligibly small possibility that the maximum credible earthquake could occur close enough to the barrier, and in such a manner, as to cause any damage to it or to the plugs in the tunnels passing through it. The possibility of serious plug damage occurring as a result of a ?direct hit? by as maller event was slightly greater, but still sufficiently remote as to be of no practical concern at all.